Does ambient air Particulate Matter have a direct impact on Cardiovascular Disease incidence in the Philippines?. (8th February 2011) - Nguyen, Q.T.; Naguib, R.N.G.; Wickramasinghe, N.; Shaker, M.H.
Developed countries, where the standards of the environment in ambient and indoor areas are in line with the World Health Organization Air Quality Standards, have widely acknowledged and are fully aware of the importance of this issue. However, many developing countries, such as the Philippines, suffer from high concentrations of ambient Particulate Matter and from high rates of mortality from Cardiovascular Disease (CVD). Therefore, the aim of this paper is to understand the possible relationships between airborne pollutants and CVD in the Philippines and to raise the awareness of the government, citizens and specialists to address this issue.